Culturally Responsive Education: Developing Lesson Plans for Vietnamese Students in the American Diaspora - Douglas, Cynthia M. (Journal of International Students, 2015)
This article focuses on the application of the philosophical principles of John Dewey and Culturally Responsive Education in the creation of lesson plans for Vietnamese students in the American Diaspora. Through a Fulbright-Hayes Program a group of teachers from the New York City Public School System and Long Island spent six weeks in Vietnam studying the language and culture in order to develop lesson plans that would address the needs of Vietnamese students in their classrooms. This study demonstrates the importance of teachers connecting with their students through the incorporation of sociocultural elements that translate to a culturally responsive curriculum, not just for students in the Vietnamese Diaspora but for all students.